GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (PT BANK PEMBANGUNAN DAERAH (BPD) SUMATERA BARAT) - Titik Efnita (Universitas Putera Batam, 2018)
This Research Aims To Uncover The Influence Of Leadership Style, Work Motivation And Work Discipline Of Employee Performance. The population of this study are all employees At PT.Bank Regional Development (BPD) West Sumatra Branch Painan which amounted to 45 people. Samples were taken from all populations of 45 people. The analysis method uses multiple regression analysis. The results obtained: Multiple effect of variable X together to variable Y at PT.Bank Regional Development (BPD) West Sumatera Painan Branch is equal to 0,573 or 57,3% with Sig. F at 0.000 <0,05 or Fthitung nilat bigger than F table that is 26,445> 3,34, hence can be said that leadership style (X1) work motivation (X2) and work discipline (X3) have positive and significant influence to Performance employees of PT.Bank Regional Development (BPD) West Sumatera Painan Branch. Partially, leadership style have positive and significant influence to employees performance of PT.Bank Regional Development (BPD) West Sumatera Painan Branch where t arithmetic variable of leadership style bigger than t table (t count 2,713> t table 1,9883) or its significance is smaller than alpha (0,010 <0,05). Partial of work motivation have positive and significant effect to employee performance of PT.Bank Regional Development (BPD) West Sumatera Painan Branch where t arithmetic variable of work motivation bigger than t table (titung 2,181> t table 1 , 9883) or its significance is less than alpha (0.035 <0.05). Partially work discipline has a positive and significant effect to the performance of employees of PT.Bank Regional Development (BPD) West Sumatera Painan Branch where t arithmetic variable work discipline is greater than t table (t count 4,636> t table 1,9883) or siginifikansinya smaller than alpha (0,000 <0.05), and the regression equation for these three variables is Ŷ = 26.445 + 0.299 X1 + 0.220X2. + 0.409 X3.